PERAN SISTEM INFORMASI MANAJEMEN DALAM MENDUKUNG PENGAMBILAN KEPUTUSAN KEPALA MADRASAH - Pitriani; Saipul Annur; Ade Rosad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study looks at how Madrasah principals' decision-making processes are supported by Management Information Systems (MIS). Effective leadership in Islamic educational institutions necessitates timely, precise, and pertinent information to make sure that choices are in line with Islamic principles like professionalism, accountability, and trustworthiness as well as institutional objectives. This study investigates how MIS is used in Madrasah institutions to manage academic, administrative, financial, and human resource data using a qualitative methodology. To obtain a thorough grasp of how information systems support data-driven decision-making, information was gathered through observations, interviews, and document analysis. The results show that by offering organized, integrated, and real-time information, MIS significantly contributes to raising the caliber of decisions. It improves institutional management's effectiveness, accountability, and transparency. Furthermore, rather than depending only on instinct, principals can make strategic and objective decisions when trustworthy data is available. In summary, MIS deployment is a strategic tool that enhances leadership effectiveness and promotes the general advancement of Islamic education administration in the digital age, rather than only a technical requirement.